Pelatihan Pengelolaan Sampah Organik Rumah Tangga Menggunakan Ember Komposter: Dampak dan Hasil di Desa Sirnasari - Kamaludin, Muhamad; Gaharani Saraswati; Mirwan Aji Soleh; Subarna; Siti Noor Rochmah (Politeknik Piksi Ganesha Indonesia, 2025)
This training examines organic waste management using composter buckets in Sirnasari Village. The purpose of the service is to improve knowledge and practice of household waste management and reduce environmental impacts through composting. Methods include participatory workshops, distribution of practical guides, and direct monitoring. The results show significant improvements in waste segregation, composter bucket use, and reduction in waste ending up in landfills. The compost produced also provides direct benefits for plant growth. This service supports the adoption of simple technologies for organic waste management in rural communities, potentially improving environmental quality and community sustainability.